Rancang Bangun Aplikasi Al-Quran dan Terjemahan Per Kata Menggunakan CI (Codeigniter) (Information Technology and Telematics, 2015)
ABSTRACT Al-Quran is a holy book of Muslims around the world. Muslims believe that holy Quran is the last revelation of Allah  given  to  human  through  the  angel Gabriel  (Jibril)  dan  delivered  to Muhammad. Related  to  the  needs  of  holy Quran  combined with the development of technology in this modern era by internet is greatly increased. It is seen by so many Al-Quran sites or websites, such as www.quranterjemah.com. But fitures provided in it needs further development because  users  see  information  of  translation  per word  by  bring  the  cursor  to  a  desired  fragment  of  verse which  is allowing users might see the wrong translation because less of thorougness in seeing. Beside that users could listen to the murotal after downloaded the file first. One of the solution for the issue above is by creating system which its focus is on the users need. The purpose of this Al-Quran application is for the time efficency and to ease users in searching information about Al-Quran. Al-Quran application  is designed by using UML  (Unified Modelling Language) and creatde by  codeigniter framework as programming languag and MySQL as database. Keywords: Al-Quran, Codeigniter, MySQL